Toward the molecular understanding of the action mechanism of Ascophyllum nodosum extracts on plants - De Saeger, Jonas; Van Praet, Stan; Vereecke, Danny; Park, Jihae; Jacques, Silke; Han, Taejun; Depuydt, Stephen (Journal of applied phycology, 2020)
The importance of biostimulants, defined as plant growth-promoting agents that differ notably from fertilizers, is increasing steadily because of their potential contribution to a worldwide strategy for securing food production without burdening the environment. Based on folkloric evidence and ethnographic studies, seaweeds have been useful for diverse human activities through time, including medicine and agriculture. Currently, seaweed extracts, especially those derived from the common brown alga Ascophyllum nodosum , represent an interesting category of biostimulants. Although A. nodosum extracts (abbreviated ANEs) are readily used because of their capacity to improve plant growth and to mitigate abiotic and biotic stresses, fundamental insights into how these positive responses are accomplished are still fragmentary. Generally, the effects of ANEs on plants have been attributed to their hormonal content, their micronutrient value, and/or the presence of alga-specific polysaccharides, betaines, polyamines, and phenolic compounds that would, alone or in concert, bring about the observed phenotypic effects. However, only a few of these hypotheses have been validated at the molecular level. Transcriptomics and metabolomics are now emerging as tools to dissect the action mechanisms exerted by ANEs. Here, we provide an overview of the available in planta molecular data that shed light on the pathways modulated by ANEs that promote plant growth and render plants more resilient to diverse stresses, paving the way toward the elucidation of the modus operandi of these extracts.